Pengembangan tes pemahaman konsep pemanasan global berorientasi lahan basah menggunakan model Rasch - Rahmadia Tiara Agusta; Ahmad Fauzan; Edwin Musdi; Suherman; I Made Arwana (Jurnal Penelitian Pendidikan IPA, 2026)
This study explores authentic numerical practices and numeracy embedded in the Maapam tradition of West Pasaman through an ethnomathematical lens. The Maapam tradition is a communal cultural practice involving the preparation, cooking, and sharing of traditional cakes called apam. Using a qualitative ethnographic approach, data were collected through direct observation and semi-structured interviews with community members who actively participate in the tradition. The findings reveal that Maapam involves various forms of mathematical and numeracy reasoning that occur naturally within everyday cultural activities. In particular, proportional reasoning and numerical scaling are demonstrated when determining the composition and quantity of ingredients according to the desired amount of apam. Practical arithmetic and budgeting are also evident during the procurement of ingredients, including estimating quantities, calculating costs, comparing prices, and managing available resources. Furthermore, spatial and numerical measurement can be observed through the use of circular molding tools, including considerations of size, diameter, quantity, and distribution. These practices demonstrate that numeracy is not merely an academic construct learned in formal educational settings but also a lived cultural competence developed through meaningful communal activities. Integrating the Maapam tradition into numeracy education can provide a culturally responsive learning context that connects abstract numerical concepts with students’ everyday experiences and local environment. Such integration may strengthen students’ numerical reasoning, problem-solving abilities, and understanding of mathematical concepts while simultaneously fostering cultural awareness, appreciation, and respect for local traditions. Therefore, Maapam represents a valuable ethnomathematical resource for developing meaningful, contextual, and culturally relevant numeracy learning in contemporary educational contexts.